Техніко-економічне обґрунтування показників якості кришення ґрунту в умовах проведення експериментальних досліджень - Волик, Борис Анатолійович; Volyk, Borys; Лепеть, Євген Іванович; Lepet, E.; Теслюк, Юлія Валеріївна; Tesliuk, Yuliia (Таврійський державний агротехнологічний університет, 2022)
В статті запропонована методика оцінки якості кришення ґрунту на основі сумісного використання коефіцієнтів структурності і різноподрібнення структурних відмінностей. Основою досліджень є математична модель взаємодії з ґрунтовим середовищем робочого органу довільної геометричної форми Враховуючи те, що кришення – це технологічна операція, яка забезпечує зменшення розміру ґрунтових відмінностей, наведені показники пропонується розраховувати за результатами статистичного аналізу фракційного складу ґрунтових відмінностей графоаналітичним методом шляхом побудови і подальшого аналізу огіви розподілу фракційного складу обробленого середовища. Введення в практику досліджень цих показників має за мету обґрунтування механізму оцінки адекватності математичної моделі взаємодії робочого органу з ґрунтом. Наведені раціональні діапазони абсолютних значень коефіцієнтів за видами обробітку ґрунту. Experimental research is mostly conducted to confirm the rationality of the developed calculation schemes and the adequacy of mathematical models. In the process of experimental research, it is first necessary to establish whether the working body ensures compliance with agronomic requirements in accordance with the type of tillage. The analysis shows that the known agronomic requirements are a compromise between the needs of plants and the technical capabilities of the working body. Agricultural requirements can be divided into generally accepted, or those used in practice in the context of agro-industrial production and special, or those used in research. The theory of internal stress is the methodological basis of the mathematical model of the interaction of the working body with the soil environment. The model provides for the production of a number of specific indicators that characterize soil crumbs. Due to the fact that these indicators are not generally accepted methods for their determination are absent. In this regard, the purpose of the article is to substantiate the method of practical determination of analytically sound coefficients of structure and different fragmentation of soil differences The proposed indicators of assessment of the quality of crushing are calculated based on the results of statistical analysis of the fractional composition of soil differences of the treated environment. The fractional composition is determined by sieving soil samples on a sieve classifier, for which within the control area is removed loose soil sample is successively sieved on sieves with a diameter of 35 to 3.5 mm Plant residues are removed. According to the results of statistical processing of the array of data obtained, the curve of accumulated frequencies (ogiva). Graphically, the maximum value of the reduced diameter of soil differences is determined, the percentage of which is respectively 10.20.60% and the percentage of units with a reduced diameter of 10.30.50 mm. The coefficient of structure is defined as the ratio of the content of agronomically valuable aggregates (0.25 - 10 mm) to the content of the sum of aggregates with a given diameter of less than 0.25 mm and lumps, more than 10 mm]; As practice has shown, the separation of units smaller than 0.25 mm makes an error of not more than 2… 3%, which is less than the accuracy of the experiment. The coefficient of variation of structural differences is defined as the ratio of the accumulated diameter of lumps of 60% by weight to the accumulated diameter of lumps of 10% by weight.
Analytical substantiation of quality indicators of soil crushing under the conditions of experimental studies
Keywords: експериментальні дослідження; experimental research; агровимоги; agricultural requirements; кришення; crumbs; ґрунтові відмінності; soil differences